2012
DOI: 10.1021/jf302958g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Solvent-Free Synthesis of Phytostanyl Esters in the Presence of Acid-Surfactant-Combined Catalyst

Abstract: An efficient approach based on the synthesis of phytostanyl esters with an acid-surfactant-combined catalyst in a solvent-free system was developed. The effect of catalyst dose, substrate molar ratio, reaction temperature, and acyl donor was considered. The reaction conditions were further optimized by response surface methodology, and a high yield of phytostanyl laurate (>92%) was obtained under optimum conditions: 3.17:1 molar ratio of lauric acid to plant stanols, 4.01% catalyst dose (w/w), 119 °C, and 4.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…In 2012, He et al prepared fatty phytostanyl laurate, a cholesterol-lowering food additive, by the esterification reaction of phytosterols with lauric acid in the presence of DS and HCl. [30] The authors reported a yield as high as 92 % after optimization of the reaction parameters. Later on, the same team extended the preparation of phytostanyl laurate to copper and cerium dodecyl sulfates (i.e., [Cu(DS) 2 ] and [Ce(DS) 3 ], respectively) as Lewis acidic surfactant-combined catalysts, which showed in all cases promising activities.…”
Section: Amphiphilic Acid/base Catalystsmentioning
confidence: 99%
“…In 2012, He et al prepared fatty phytostanyl laurate, a cholesterol-lowering food additive, by the esterification reaction of phytosterols with lauric acid in the presence of DS and HCl. [30] The authors reported a yield as high as 92 % after optimization of the reaction parameters. Later on, the same team extended the preparation of phytostanyl laurate to copper and cerium dodecyl sulfates (i.e., [Cu(DS) 2 ] and [Ce(DS) 3 ], respectively) as Lewis acidic surfactant-combined catalysts, which showed in all cases promising activities.…”
Section: Amphiphilic Acid/base Catalystsmentioning
confidence: 99%
“…4a, the conversion of octacosanol reached 90.9 ± 3.6 % at 1:1 molar ratio of octacosanol to linoleic acid. Generally speaking, the esterification reactions were reversible, the increase of the amount of one substrate could promote the occurrence of the esterification reaction and shift the reaction equilibrium toward the products [25]. However, the conversion rate was not significantly increased with the increase of the molar ratio of octacosanol to octacosanol linoleate from 1:1 to 1:1.5 (P > 0.05).…”
Section: Effect Of Substrate Molar Ratio and Reaction Timementioning
confidence: 90%
“…However, the practical use of the sterols in other foods has been greatly limited by their poor solubilities [1,91]. Esterification of ergosterol is, therefore, performed to make it fat-soluble and easy to incorporate into food products [91,92].…”
Section: Oxidation Resistance Of Lanosterol and Ergosterolmentioning
confidence: 99%